KEPATUHAN HUKUM DALAM STRATEGI PENGEMBANGAN PRODUK PT INDOFOOD CBP SUKSES MAKMUR TBK: STUDI KUALITATIF PADA INDUSTRI MAKANAN DAN MINUMAN: KEPATUHAN HUKUM DALAM STRATEGI PENGEMBANGAN PRODUK PT INDOFOOD CBP SUKSES MAKMUR TBK: STUDI KUALITATIF PADA INDUSTRI MAKANAN DAN MINUMAN - Jihan Aziz Wulandari; Kevia Dela Agustin; Selvia Oktaviza; Renaldi Pradwika; Muhammad Syaiful Anwar (Jurnal Pijar, 2023)
This qualitative study examines the legal compliance in the product development strategy of PT Indofood CBP Sukses Makmur Tbk within the food and beverage industry. The research aims to explore and analyze the extent to which the company adheres to legal regulations in their product development approach. The study employs a qualitative research design, utilizing descriptive and interpretive methods to examine the strategies employed by PT Indofood CBP Sukses Makmur Tbk in expanding their product offerings. Data collection involves document analysis, interviews with relevant stakeholders, and direct observation of company activities. The findings of this study contribute to a better understanding of the company's compliance with legal regulations and shed light on the implications of their product development strategies within the legal framework. This research provides valuable insights for legal practitioners, business decision-makers, and regulators, enabling them to comprehend the legal challenges and opportunities within the food and beverage industry.